The Islamic Education In Responding To The Barrenness Of Information Technology - Mahmuda Mahmuda (EDUCATIO : Journal of Education, 2018)
This research aims to find the extent of Islamic education in addressing and follow the flow of information technology. the progress in information technology has resulted in massive changes in human culture. As part of the world community, at the same time Muslims growing niche to be less-able to keep abreast of the times. Moreover if you want to Compete of other nations in the mastery of science and technology to change towards a better life. Certainly it is more complicated. It all proved by few problems in general items, namely how to prepare the young generation who are very Easily influenced by the flow of information technology while the foundation is not solid faith, to have the ability in the future to address all the challenges they face adequately through Islamic education. The results Showed that 1) an Islamic education both institutionally and in the education system of the nation's children must work in synergy among families, institutions, government and the community to be well controlled. Because of to repair a nation's moral obligation is not only an obligation but Also Islamic education obligation of all parties. While the position of Islamic education is as neutralizer between technology and reality. 2) the role of teachers to educate students to be human is always with the times without leaving the roots are very important in Determining the nation's next trip. 3) The role of the government as controller movement of information technology is always evolving in order to continue to conduct monitoring and analysis with more specific to the problem in society. Overall this aspect shows that between Islamic education and technology must always be paired with continuous control by implementing three key controlling Islamic education to the technology that is commanding the good, nahi unjust, and faith